Alkali metal-modified crystalline carbon nitride for photocatalytic nitrogen fixation - Li, Yang; Wang, Baibing; Xiang, Quan-Jun; Zhang, Qin; Chen, Gui (Dalton transactions : an international journal of inorganic chemistry, 2022)
Alkali metal chlorides have been used as molten salts for further preparing crystalline carbon nitride, but the effect of alkali metal types on the properties of crystalline carbon nitride has not been systematically studied. Therefore, in this paper, a series of crystalline carbon nitride samples doped with different alkali metals were successfully prepared using LiCl-KCl, KCl-NaCl, LiCl-KCl-NaCl and LiCl-NaCl as molten salts: LK-HTCN (Li-K co-doping), KN-HCN (K-Na co-doping), LKN-HTCN (Li-K-Na co-doping) and LN-HTCN (Li-Na co-doping). The experimental results show that KN-HCN contains only the heptazine unit structure, while the other samples contain heptazine and triazine unit structures. Meanwhile, the concentration of the cyano group in the KN-HCN sample structure is significantly higher than that of other samples, which may be related to the fact that there is only a heptazine unit in the structure of the KN-HCN sample. In addition, the loading mode of K and Na ions in the KN-HCN structure is favorable for the migration and separation of photogenerated charges. Thanks to these characteristics, KN-HCN showed excellent photocatalytic ammonia production activity. This study can provide theoretical insight for the development of crystallized carbon nitride. KN-HCN exhibited enhanced photocatalytic ammonia production because of the presence of a large number of cyano groups and the loading mode of potassium and sodium ions.